Facilitation in an intractable peace process: Understanding Norwegian commitment to the GRP - CPP/NPA/NDFP peace negotiations - Andaya, Raymond M. (Animo Repository, 2017)
The Royal Norwegian Government has been facilitating the ongoing peace process between the GRP and the CPP/NPA/NDFP since 2001. This thesis aims to contribute to the literature by scrutinizing Norway's facilitation of the peace process using the theory of mediation as political problem solving. Assumptions on what makes a particular mediator acceptable and what preconditions are crucial for mediation success, are considered. To assess the impact of Norway's facilitation strategy, the two most common categories of mediation success were utilized: mediation as settlement and resolution. In this thesis, settlement refers not only to efforts to reduce or eliminate the destructive sort of conflict generating behavior, but also the attempts to deal with non-substantive agenda issues that are also symptoms of the conflict. On the other hand, resolution refers to efforts to address the root causes of the conflict, or more specifically, the four substantive agenda issues (human rights and international humanitarian law, socioeconomic reforms, political and constitutional reforms, and end of hostilities and disposition of forces) recommended by the 1992 Hague Joint Declaration. Norway's success in facilitating the peace process was analyzed through the contingency between contextual variables (characteristics of the dispute, parties and their interrelationship, characteristics of the mediator, and the international context) and the process variable, or the mediators activities. A typology of stylistic dimensions is used to specify the nuances of Norwegian facilitation. This thesis finds that Norway's facilitation strategy has been ineffective, both as a method of settlement and resolution. Nonetheless, the facilitated peace process was able to make significant strides as a result of the agreement to accelerate negotiations of the substantive agenda. Through an analysis of the dynamics of contextual and process variables, findings indicate that Norway's inadequacy to make significant impact is not a function of its limited operational mandate. Rather, it is the context of the facilitation effort that inhibits the likelihood of success in the peace talks. The most significant contextual factors for both categories of mediation impact include: (1) the inability to sustain conflict ripeness when both parties exhibit conciliatory behavior at the beginning of each new GRP administration (2) the disconnect between the peace objectives during formal talks and the continued violence on the ground and (3) perceptions of the insurgency and minimal public interest in the peace process.